DRAWING FOR PRODUCT DESIGNERS - Henry, Kevin (Portfolio skills. Product design, 2012)
This is both a practical and theoretical guide to the visualization techniques used by contemporary product designers, including freehand sketching, digital rendering, information graphics, and presentation skills.